Rehabilitative Surgery A Comprehensive Text for an Emerging Field - Elkwood, Andrew I.; Kaufman, Matthew; Schneider, Lisa F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book represents the first interdisciplinary text on the emerging field of rehabilitative surgery, in which state of the art procedures from multiple surgical specialties are combined. It proposes a completely new framework for understanding, coordinating, and providing treatment for paralyzed or severely neurologically impaired patients and explains the potentially critical impact of surgery in creating a new baseline of functional status, thereby improving the patient$1 (Bs daily life. Every major aspect of reconstructive surgical treatment is considered, including anesthesia, orthopedic surgery, plastic surgery, neurosurgery, general surgery, vascular surgery, and otolaryngology. The most up-to-date and evidence-based surgeries are clearly described and evaluated, with coverage of treatment of pressure sores, placement of feeding tubes, and upper extremity interventions to improve function and hygiene. Cutting-edge protocols are presented for the surgical treatment of severe nerve injuries, spinal cord injuries, and stroke or cerebrovascular accidents, and a first description and evaluation of phrenic nerve repair to assist weaning of paralyzed patients from ventilators is provided. Both surgical and nonsurgical readers will find this book to be an ideal guide and reference.s
I-Introduction -- 1.Introduction to Rehabilitative Surgery -- 2.Introduction to Surgical Principles -- II.Anesthesia -- 3.Anesthetic Considerations in Rehabilitative Surgery -- 4.Deep Venous Thrombosis in the Operative Rehabilitation Patient -- III.Pain management -- 5.Evaluation and Management of Chronic Pain -- IV.Nervous system and spine -- 6.Neurosurgical Overview -- 7.Neurologic Injury and Spasticity -- 8.Electrodiagnostic Testing for Nerve Injuries and Repairs -- 9.Spine Trauma -- V.Airway, Thorax and Abdomen -- 10.Phrenic Nerve Reconstruction for Diaphragmatic Paralysis and Ventilator Dependency -- 11.Physical Therapy Following Phrenic Nerve Graft Surgery: Implications Far Beyond Breathing -- 12.Recovery of Diaphragm Function through Functional Electrical Stimulation: Diaphragm Pacing -- 13.Acute and Long-Term Surgical Management of the Spinal Cord Injury Patient -- 14.Surgical Reconstruction of Pressure Ulcers -- 15.Acute Burn Management and Rehabilitation -- VI.Reanimation of the paralyzed extremity -- 16.A Global Approach to Upper Extremity Paralysis: The Role of Surgery in Limb Reanimation -- 17.Amputation vs. Limb Salvage of the Lower Extremity -- 18.Surgical Rehabilitation of the Tetraplegic Upper Extremity -- 19.Lower Extremity -- 20.Inguinal Pathology -- 21.Hand Transplantation and Rehabilitation -- 22.Targeted reinnervation strategies to restore upper limb function -- VII.Orthopedic surgery -- 23.Orthopedic Considerations in Rehabilitative Surgery -- 24.Upper Extremity Neuromuscular Disorders -- VIII.Urologic surgery -- 25.Surgical Considerations in Neurogenic Bladder -- IX.Vascular considerations, including lymphedema -- 26.Vascular Considerations in Rehabilitative Surgery -- X.Future directions -- 27.Spinal Cord and Peripheral Nerve Regeneration Current Research and Future Possibilities.
Keywords: Medicine; Neurosurgery; Orthopedics; Otorhinolaryngology; Rehabilitation; Surgery; Urology; Medicine & Public Health; Surgery; Neurosurgery; Surgical Orthopedics; Otorhinolaryngology; Urology; Rehabilitation